Las novelas de la Transición de Juan José Millás: "Cerbero son las sombras", "Visión del ahogado", "El jardín vacío" - Luigi Contadini (Impossibilia: Revista Internacional de Estudios Literarios, 2013)
This paper analyses the first three novels by Juan José Millás. They can be named Transition novels since they are both chronologically close to the most significant steps of the democratic process andfor the themes they approach, themes that hint at those multifaceted issues, uncanny and gloomy, that every age leaves at the margins of the public sphere. Through an investigation of the narrative strategies –with specific reference to time and enunciation– the essay highlights the most significant cruxes of those years, still partly unsolved and emblematically represented by characters in pain, trapped in a heavy memory; characters who desire a way out, but marked by the impossibility to envisage their own future.